Droopy rice suppresses weeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Rice farmers in West Africa may soon have rice varieties with droopy lower leaves and erect top ones.